Effectiveness Of Detention Ponds For Flood Mitigation Project : A Case Study For Sungai Pechong, Tanah Merah, Kelantan - Sarento Pangilan, Rayhana (2014)
Flood occurrences are becoming widespread all over the world as the level of urbanization has increased tremendously especially in the recent years. This problem is further aggravated by inappropriate urban drainage systems built in developing areas. The government of malaysia has taken proactive steps to address these flooding issues as the country is envisioned to be a fully developed nation in 2020 by implementing the urban stormwater management manual for malaysia (msma). One of the significant best management practices (bmps) identified in the msma was the construction of detention ponds for flood mitigation. Implementation of this structure has proven functional in alleviation of flood problems especially in areas downstream.